Phantom energy mediates a long-range repulsive force - Amendola, Luca (Arxiv, 2004)
Scalar field models with non-standard kinetic terms have been proposed in the context of k-inflation, of Born-Infeld lagrangians, of phantom energy and, more in general, of low-energy string theory. In general, scalar fields are expected to couple to matter inducing a new interaction. In this paper I derive the cosmological perturbation equations and the Yukawa correction to gravity for such general models. I find three interesting results: first, when the field behaves as phantom energy (equation of state less than -1) then the coupling strength is negative, inducing a long-range repulsive force; second, the dark energy field might cluster on astrophysical scales; third, applying the formalism to a Brans-Dicke theory with general kinetic term it is shown that its Newtonian effects depend on a single parameter that generalizes the Brans-Dicke constant.